Realising the Rights of Persons with Disability in Nepal: Policy Addresses From the Health, Education and Livelihoods Perspectives - Adhikari, Keshab Prasad (Nepalese Journal of Development and Rural Studies, 2019)
Review of national policies and legislative measures made for the protection, prevention, promotion and rehabilitation rights of persons with disabilities in Nepal to most part adhered to international measures developed in the field. Protection and welfare act of persons with disabilities was introduced in 1982-83 in the country. The Constitution of Nepal-2015 gave ample space to the concerns of persons with disability; accordingly government prepared National Act related to the rights of the persons with Disability-2017. The Act explicitly outlined objectives, policy measures and action plans to establish the health rights, education rights and right to livelihood, skill development and employment of the persons with disabilities. Health rights include preventive, promotive, curative and rehabilitative issues along with right to sexual and reproductive health rights, management of pelvic organ prolepses and reproductive impairments of women and girls with disabilities. Still problem lies in collection and compilation of health information by disability status of persons. The National Childhood Disability Management Strategy (CDMS) – 2008 offered policy measures for the detection, management and prevention of further impairments of childhood disabilities reaching at the door-steps where it occurs. Government introduced inclusive education policy and policies of disability friendly livelihood/skill development and employment policies. However, implementation of the policy measures still in problem due to clarity lacks in policies regarding roles and responsibilities by levels of governments from local to federal governments.